2016
DOI: 10.1080/09638237.2016.1244722
|View full text |Cite
|
Sign up to set email alerts
|

College students’ stigmatization of people with mental illness: familiarity, implicit person theory, and attribution

Abstract: Educational campaigns may be effective by focusing on aspects of MI highlighting similarity with non-diagnosed people, and that people with MI can recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 37 publications
4
29
1
2
Order By: Relevance
“…Students' acquisition of psychiatric skills and psychiatric rotation showed limited effects on students' prejudices about people with schizophrenia, and on their pessimism about recovery (38)(39)(40). Other studies found that psychiatric knowledge was useful to improve students attitudes towards people with mental disorders and their confidence with psychiatric drugs (38,(41)(42)(43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students' acquisition of psychiatric skills and psychiatric rotation showed limited effects on students' prejudices about people with schizophrenia, and on their pessimism about recovery (38)(39)(40). Other studies found that psychiatric knowledge was useful to improve students attitudes towards people with mental disorders and their confidence with psychiatric drugs (38,(41)(42)(43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…For depression, psychological treatment approach was recommended electively (39). Finally, a USA study on stigma toward people with mental disorders in 159 undergraduate psychology students (40) reported that participants who felt personality traits were unchangeable were more likely to stigmatize individuals with mental disorders and desired more social distance. The study also revealed that biogenetic causal attribution was related to higher stigma, but not so when familiarity with people with mental disorders and perception of personality trait as unchangeable were taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…People who see traits as dimensional instead consider a multitude of variables and display more fine-grained, shades-of-gray thinking; they view intelligence as something to be developed over time (Chiu et al 1997;Hong et al 1995). With their dynamic view of the world, these dimensional thinkers accept inconsistencies and change (Lyndon et al 2016;Plaks et al 2001). Such implicit worldviews in turn affect people's judgments, motivation (Jain et al 2009), affect regulation (Labroo and Mukhopadhyay 2009), and education (Ambrose 2017); they also extend beyond personality traits to affect health-related beliefs (Wang et al 2009).…”
Section: Implicit Worldviews As Antecedents Of Public Stigmamentioning
confidence: 99%
“…Therefore, we draw on theories of implicit worldviews, that is, the perceptions that people hold about themselves and others that determine whether they perceive their environment as categorical or dimensional (Chiu et al 1997). These viewpoints inform attitude formation and decision making, especially in relation to stereotypes and stigmatizing attitudes, and affect how people process new information (Lyndon et al 2016;Plaks et al 2005). Through this substantive theoretical lens, we examine some causes of public stigma and some previously unexamined effects that might inform stigma reduction strategies.…”
mentioning
confidence: 99%
“…Medical students believe that persons with mental illness are unpredictable (Magliano, et al, 2013) The presence of stigmatizing attitudes in psychology students has been found in many studies, and it is increasing with time. For example, Lyndon and colleagues (Lyndon et al, 2016) determined that psychology students who believe that personality traits are unchangeable are more likely to stigmatize individuals with mental disorders and desire more social distance from them. The same study showed that being close to a person with a psychiatric disorder is a predictor of reduced social distance.…”
Section: Introductionmentioning
confidence: 99%